Cristián Gazmuri R. La historiografía chilena (1842-1970). Tomo II - Villalobos R., Sergio (Cuadernos de Historia, 2012)
Centro de Investigaciones Diego Barros Arana. Taurus, Santiago, 2009, 481 páginas. ISBN 978-956-239-628-8.